Epidemiology of Primary Headaches Among 1, 876 Adolescents: A Cross-Sectional Survey. Issue 2 (25th November 2015) - Sedlic, Marija; Mahovic, Darija; Kruzliak, Peter
Abstract : Background . The main goal of our research was to perform an epidemiological study of migraine and tension-type headache (TTH) among high school students in the Republic of Croatia. Methods . The authors surveyed 1, 876 students attending high schools in the Republic of Croatia using a self-administered 36-item questionnaire. Results . Among 1, 876 students who completed the questionnaire, prevalence of migraine was 12.8% (17% in women and 8.1% in men) and prevalence of TTH was 38.3% (40.6% in women and 35.7% in men). Prevalence of migraine with TTH was 2.9% (3.1% in women and 2.7% in men). The authors found a significantly greater prevalence of migraine in female than in male students (OR = 2.3), as in TTH (OR = 1.23). Compared with students with TTH, migraine sufferers were more inclined to take medications (OR = 3.29) and use health care (OR = 8.12) and were more likely to smoke (OR = 2.34). Conclusion . The prevalence of primary headaches in Croatia is similar to that in other countries of the world. TTH is the most common primary headache, occurring later in relation to migraine, and both types are more common in females. Teenagers who suffer from migraines are more likely to smoke in comparison to TTH. Although migraine patients visit the doctor and take medications more frequently than those with TTH, both headaches are being underdiagnosed and undertreated.